Direct Electrochemical Synthesis of Sulfur‐Containing Triazolium Inner Salts. Issue 4 (29th March 2021) - Li, Yueheng; Huang, Zhixing; Mo, Guangquan; Jiang, Wei; Zheng, Chengwei; Feng, Pengju; Ruan, Zhixiong
Main observation and conclusion: The electrochemical thiocyanation/cyclization of aldehyde hydrazones was developed under external oxidant‐free and catalyst‐free conditions. In contrast to previous thiocyanation, this electrosynthetic approach enabled a cascade C—H thiocyanation/cyclization through a mild, direct electrolysis manner in an undivided cell without the additive of halogens and stoichiometric oxidants. In this protocol, commercially available and inexpensive sodium thiocyanate was used, which played a dual role as a thiocyanation reagent and electrolyte. This strategy provides expedient access to functionalized sulfur‐containing triazolium inner salts with ample scope and diverse functional group tolerance. Based on the findings of mechanistic studies, a reaction mechanism was proposed. Abstract : In this protocol, functionalized triazolium inner salts are achieved through the electrochemical thiocyanation and cyclization of aldehyde hydrazone derivative with ample scope and diverse functional group tolerance, under mild, catalyst‐ and external oxidant‐free conditions.